Piloting a peer literacy program: Implications for teacher education - Miciano, Remedios Z. (Animo Repository, 2006)
To pilot a peer literacy program, a pretest-posttest study was conducted involving seventy (70) students from Arellano High School as tutees and 12 De La Salle University-Manila College of Education students as reading tutors. Though the results suggest the lack of impact of the Program on the Reading Grades of the tutees, the tutors' journals reveal that the tutors benefited more from the program. The problems in using the National Service Training Program or NSTP as the vehicle in piloting the program were identified and based on this, the study suggests ways to improve the content and delivery of future NSTP Peer Literacy Programs. Copyright 2006 by Education Research Institute.